2023
DOI: 10.3390/fluids8020035
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Dynamics of Miscible Displacement of Shear-Thinning Fluid in a Vertical Channel

Abstract: The displacement of a shear-thinning fluid by a denser and less viscous Newtonian fluid in a vertical duct is investigated using experiments and numerical simulations. We study how shear-thinning and increased viscosity contrast between the fluids affect the displacement. Our results show that the degree of shear-thinning significantly influences the development of interfacial patterns and the growth of perturbations. In the weakly shear-thinning regime, the displacement progresses as a stable displacement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…We observed that the NSH suspensions exhibited non-Newtonian behavior of the dilatant type, with a behavior index (n) greater than 1.00 (Table 2). This indicated that their apparent viscosity increased with the deformation speed, resulting in enhanced thickening, more stability and reduced dispersion [54]. Such behavior arises from molecular interactions among hydrocolloid particles when subject to external stresses.…”
Section: Suspended Solid Stability Of Nsh Suspensionsmentioning
confidence: 97%
“…We observed that the NSH suspensions exhibited non-Newtonian behavior of the dilatant type, with a behavior index (n) greater than 1.00 (Table 2). This indicated that their apparent viscosity increased with the deformation speed, resulting in enhanced thickening, more stability and reduced dispersion [54]. Such behavior arises from molecular interactions among hydrocolloid particles when subject to external stresses.…”
Section: Suspended Solid Stability Of Nsh Suspensionsmentioning
confidence: 97%